Dunstan : saint and statesman - Dales, Douglas (James Clarke & Co., 2013)
St Dunstan of Canterbury (909-88) was the central figure in the development of English church and society after the death of King Alfred. Douglas Dales traces Dunstan's life beginning with his education at the great monastery of Glastonbury of which he became abbot. He was a central figure at the court of the kings of Wessex but was banished, partly because of his hostility to the king's mistresses, and went to exile in Flanders. After his return he was appointed Archbishop of Canterbury. During the twenty-eight years of his primacy he carried out one of the major developments of the century,